(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
Code switching is a widely observed but less studied phenomenon, especially in multilingual and multicultural communities. So, the present study investigated the status of grammatical code switching among Iranian EFL university students. Also, the role of the teacher in managing the code switching was investigated, too. Two classes including 96 participants from two different universities were observed carefully and the required data were collected. Analyses of the data revealed varying nature of code switching in both settings. Moreover, the obtained frequencies revealed the fact that among the four types of trigger words only proper nouns and discourse marker ˜OK remarkably were responsible for code switching in one setting, while ˜lexical transfer and also the discourse marker ˜OK lead to code switch in another. Meanwhile, four functions for code switching were determined, which included providing equivalents for the key word, showing humor, inspiring learners, and explaining the required assignments, as teachers role in dealing with code switching .